Media Literacy in Virtual Communication: A Case Study on the YouTube Channel @gurugembul - Rifqi Zaeni Achmad Syam; Ani Yuningsih (Jurnal Komunikasi Pendidikan, 2025)
This study was motivated by the challenges society faced in filtering valid information in the digital era, especially among young people. The YouTube channel @gurugembul played an important role in improving media literacy through the delivery of interactive educational content. The purpose of this study was to analyze how the @gurugembul YouTube channel delivered educational information using an interactive virtual communication approach. The method used was a qualitative approach with a case study design, which involved interviews with content creators and document analysis of the videos produced. The findings showed that the @gurugembul YouTube channel successfully selected relevant topics and presented them in a relaxed and easily understandable communication style, which encouraged active audience participation. The study concluded that interactive and educational communication approaches enhanced the audience's understanding of important social issues. This research contributed to the field of education by providing insights into the use of digital platforms in the learning process and effective communication strategies to improve media literacy among young people. Recommendations for further research were also made, focusing on the long-term impact of audience interaction with educational content.